Synthesis, evaluation of antimicrobial activity, and DFT analysis of 1-(4,5-diphenyl-1H-imidazol-2-yl)naphthalen-2-ol - K, Pruthviraj; B S, Chethan; T N, Lohith; N S, Dinesh Babu; R, Chandrakumar; Kumar, Mohan; G, Shivaraja; K, Sunil (Indian Journal of Pharmacy & Drug Studies, 2024)
In the present work, we report synthesis of 1-(4,5-diphenyl-1H-imidazol-2-yl)naphthalen-2-ol an asymmetric catalytic block, fluro-phore and pharmacologically potent triaryl imidazole derivative having naphthalene ring via solvent free eco-friendly method using Debus-Radiszewski condensation reaction of benzil with 2-hydroxy napthaldehyde in presence of molecular iodine as the catalyst and ammonium acetate as the source of nitrogen this method offered the compound in good yield compared to conventional method. The structure of the compound was established based on FTIR, multi nuclear NMR (1H &13C) spectral data and mass spectrometry. Pharmacological potency was evaluated through in-vitro antimicrobial activity against four different bacterial strains (Gram-ve bacteria K aerogenes, E coli, P desmolyticm, Gram+ve bacteria S Aureus) and two strains of fungi (A flavus and C albicans) exhib-iting potent Zone of inhibition of 500μg/50μl and 10μg/50μl respectively in comparison with the standard drugs, followed by in silico ADME evaluation obeying the Lipinski’s rule, molecular docking studies with the binding energy of -8.3 kcal/mo and -8.8 kcal/mol against docked antifungal and antibacterial protein respectively established the good agreement with the in-vitro result. Density functional theory (DFT), electro static potential diagram (ESP) and other computational techniques were utilized to analyze the physicochemical parameters like energy gap, ionization energy, and electron affinity successfully.